Conducta obstétrica en primigesta de 36 años con amenaza de parto pretérmino con 30 semanas de gestación. - Contreras Merchán, Josué Salvador (2022)
Preterm birth is one of the most common obstetric problems in public health, having an incidence of about 10% in our country, despite the efforts made by the public health sector on the importance of family planning, many of these efforts are in vain since most of the population does not plan their pregnancies and as we know good planning helps to determine what the risks are in a pregnancy and thus we can act better before a risky pregnancy allowing the pregnancy to come to term. Factors such as anemia, premature mangrin rupture, vaginal infections, preeclampsia among many more that we will detail throughout this investigation are the most frequent to produce a preterm pregnancy. For this reason, it was decided to study and follow up this pathology in the case of a 36-year-old patient, primigravida with threat of preterm labor with a gestational age of 30 weeks, the same one who presented at the Babahoyo General HospitalThe management and follow-up of this case was together with the evolution of the pregnancy, both the pertinent controls, ultrasounds, monitoring and maternal-fetal surveillance, these data being provided by the Babahoyo General Hospital. This document presents the situation faced by the health professional and the mother-child binomial due to serious adverse situations that complicate pregnancy, and on certain occasions the best moment for its termination must be chosen, with the objective that the affectation to the maternal-fetal binomial is not extreme.